(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is devoted to the methodology of teaching independent work on the subject "Algebra and Number Theory". Some examples of independent work are given for 1-year students in the direction of the methodology of teaching mathematics. It describes the features of the methodology for performing examples in the subject “Algebra and Number Theory”.